The TEN-E regulation: Allowing a role for decarbonised gas - Katja Yafimava (The Oxford Institute for Energy Studies, 2022)
The original TEN-E Regulation, adopted in 2013, established the regulatory framework for the development of cross-border energy infrastructure within the EU. Following the publication of the EU Green Deal in 2019, the EC proposed to revise the Regulation to facilitate the access of renewable and low carbon gases to the energy system by enabling hydrogen infrastructure to benefit from PCI status and thus faster permitting and EU financial assistance. This paper analyses the final Regulation as well as the evolutionary journey from the EC Proposal to the final Regulation. The paper finds that the final Regulation enables and supports 'hybrid' decarbonization, which would allow renewable hydrogen to be maximized while low carbon hydrogen is allowed to play a role which allows for renewable hydrogen to be phased in more quickly, thus helping to meet the EU GHG emissions reduction targets. Nonetheless, it remains unclear whether low carbon hydrogen will play an important role in the European energy transition. The combination of (a) natural gas being politically unpopular and expensive, (b) too few CCUS projects making substantial progress, (c) the EU's unequivocal political preference for renewable hydrogen, makes low carbon hydrogen progress less likely. Overall, the Regulation provides a positive contribution towards a regulatory framework for the decarbonization of the EU's natural gas infrastructure. It allows more time for doing so compared to the original EC Proposal and provides additional instruments for developing low carbon hydrogen. But it also confirms that unless low carbon hydrogen projects receive financial support and make significant progress before 2030, they are unlikely to happen at all. In fact, these projects would only be possible if investment is made now - rather than in the mid-2020s when Renewable and Natural Gases and Hydrogen Acquis is expected to be adopted. As private investors might be reluctant to invest and EU Member States might be reluctant to support these investments (at least until such time as the Acquis provides more clarity) and as the Regulation does not envisage significant EU financial support, any major low carbon hydrogen contribution towards meeting EU 2030 GHG emissions reduction targets is far from assured.
Keywords: 330; Biomethane; CCS; CCUS; CEF; electrolysers; EU Green Deal; European Climate Law; European Hydrogen Backbone; GHG Emissions; Hydrogen Strategy; low-carbon hydrogen; offshore grid; PCI; Pipelines; PMI; Renewable and Natural Gases and Hydrogen Acquis; Renewable hydrogen; repurposing; smart gas grid; TEN-E Regulation